2015
DOI: 10.1007/s11205-015-0896-7
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Recalling Childhood Socio-economic Status: The Role of Anchoring and Household Formation in South Africa

Abstract: In the absence of longitudinal data that track individuals over an extended period of time, information on childhood socioeconomic status can be provided by questions that ask adults to recall their parents' education or their economic status at childhood. The usefulness of these data, however, requires that people are willing to report this information, and that these reports do not vary systematically over time, for example in response to changes in current circumstances. In this paper, we evaluate recall da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Although ours is not the first study to examine the indirect validity, recall bias, or mediation via mental health (Gerlsma et al, 1997;Hardt et al, 2010;Robins et al, 1985;Sheikh, 2018a;von Fintel and Posel, 2016) in the association between CD and morbidity, the present study offered two advantages. First, we assessed the independent associations in a large representative sample of adult men and women, which facilitated the stratification of results by tertile age groups (Lindsay et al, 2004).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although ours is not the first study to examine the indirect validity, recall bias, or mediation via mental health (Gerlsma et al, 1997;Hardt et al, 2010;Robins et al, 1985;Sheikh, 2018a;von Fintel and Posel, 2016) in the association between CD and morbidity, the present study offered two advantages. First, we assessed the independent associations in a large representative sample of adult men and women, which facilitated the stratification of results by tertile age groups (Lindsay et al, 2004).…”
Section: Discussionmentioning
confidence: 85%
“…Recent changes in psychopathology and symptomatology may provide a new anchor (Haas, 2007;von Fintel and Posel, 2016) for remembering and evaluating CD. For instance, people who have more problems in adulthood might report more problems when reflecting on their childhood (Susser and Widom, 2012, p. 674).…”
Section: Introductionmentioning
confidence: 99%
“…As the survey was conducted at age 23, there is a concern that the detailed schooling history (track choice, end of year evaluations, and timing of school dropout or graduation) is affected by recall bias (Beckett, Da Vanzo, Sastry, Panis, & Peterson, 2001;Sudman, Bradburn, & Schwarz, 1997;von Fintel & Posel, 2016). In order to minimize this bias, the survey contained a detailed calendar with a line for each school year, which the respondents were asked to complete line by line in a face-to-face interview.…”
Section: Data and Samplementioning
confidence: 99%
“…Prior research has addressed this concern to some extent. For instance, von Fintel and Posel (2016) analyzed reports of recalled childhood socioeconomic position from the same sample of adults, collected two years apart. They found that recall of past SSS was fairly consistent (63% agreement), a figure similar to retrospective recall of a more objective measure, parental education (72% agreement).…”
Section: Discussionmentioning
confidence: 99%